IMPLEMENTASI MODEL EVALUASI PROGRAM CIPP (CONTEXT, INPUT, PROCESS,PRODUCT) DALAM PENYELENGGARAAN DAN PELAKSANAAN PEMBELAJARAN DI SD MUHAMMADIYAH WIROBRAJAN 3 - Eko Budi Santoso; Roihan Sadad (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Program evaluation is an important aspect in the world of education to assess the effectiveness and relevance of a program in achieving the desired goals. One of the evaluation models that is often used is the CIPP (Context, Input, Process, Product) model, which assesses not only the final results but also various aspects of its implementation. This model offers a systematic approach that allows data-based decision making to improve the quality of programs in the future. This study uses a descriptive qualitative approach and is analyzed using the CIPP model. Data were collected through observation and documentation as well as from various sources such as books, journals, and digital media, then analyzed systematically to obtain complete information. The results of the study show that the CIPP model has the advantage of providing a comprehensive evaluation, covering aspects of context, input, process, and product. This model can help identify supporting and inhibiting factors of a program and provide solutions for future improvements. However, the application of this model also has weaknesses, such as the need for large resources and the tendency to focus more on the needs of decision makers than on conditions in the field. Therefore, careful consideration is needed in applying the CIPP model so that program evaluation can run effectively and efficiently.